Prevalence and Risk Factors of Strabismus in a UK Multi-ethnic Birth Cohort. (1st October 2016) - Bruce, Alison; Santorelli, Gillian
ABSTRACT: Purpose: To determine the prevalence, types and early-life risk factors associated with strabismus in a multi-ethnic birth cohort of children aged 4-5 years in the first year of school. Methods: Data were collected prospectively over a 3-year period (2012-2015) from children participating in the vision screening program provided by orthoptists and carried out in schools located in the city of Bradford, UK. Prevalence of strabismus was determined for 17, 018 children aged 4 to 5 years. Data linkage was undertaken for 4563 children participating in the Born in Bradford birth cohort study and the vision screening program. 4067 children had complete data and were included in the multivariable regression analyses to determine associated factors. Results: 401/17018 (2.4%) children were found to have either a constant or an intermittent strabismus; 179/401 (45%) had an esotropic deviation, 214 (53%) an exotropic deviation, and 8 (2%) had a vertical deviation. No significant difference in the overall prevalence of strabismus was found between the white British, Pakistani, or children of other ethnic origin ( P =0.41). Multivariable analysis showed that children of white British ethnicity have twice the odds of having esotropia (OR 2.4, 95% CI: 1.1, 5.3). The odds of having esotropia were highest in children with a hyperopic mean spherical equivalent (OR 2.0, 95% CI: 1.7, 2.6). There was some evidence of an interaction between ethnicity and mean spherical equivalent in children with esotropia ( P =0.058). Conclusions: Prevalence of strabismus is consistent with other population-based studies in this cohort of children aged 4-5 years. Prevalence of esotropia (constant or intermittent) is greater in the white British population, odds of esotropia increased with increasing hyperopic refractive error in both white British and Pakistani children. Exotropia (constant or intermittent) was not found to be associated with refractive error, ethnicity, or other early life factors.